Portraying mathematics pre-service teachers’ experience of creating video lessons with portable interactive whiteboards through the TPACK - Bonafini, Fernanda Cesar; Lee, Younhee (The New Educator, 2021)
This study investigates how pre-service teachers use their knowledge of technology, mathematics, and pedagogy to create video lessons using portable interactive whiteboards. The TPACK framework was used to identify the different types of knowledge pre-service teachers rely on as they create their videos. Results indicate pre-service teachers’ effective use of conveyance technology, pedagogical techniques, and mathematical representations using technology. Their videos portray their process of coordinating their TPACK. Recommendations are made for teacher educators to integrate technology in activities that aim to develop pre-service teachers’ comfort and confidence with technological tools for teaching and learning. © 2021 ATE and CCNY.
0 citations (Crossref) [2023-10-31]
Keywords: dept.mat; peer-reviewed